Masakra stambulskich psów (1910) a rzeź Ormian (1915) – czyli zbrodnie zapomniane (antycypacja, analogia, nadużycie?) - Jarzyna, Anita (Slavia Occidentalis, 2015)
The main aim of the article is to conduct a comparison between the Armenian Genocide (1915) and the Hayırsızada Dog Massacre (1911). The second event is practically forgotten. Many people think that the story of how all the stray dogs in Istanbul were trapped and sent to a desert island, Sivriada, where they died due to hunger and thirst, is only a urban legend. However, it’s a historical fact, similar to the death marches of the Armenians. Both animals and people were killed in the same way – they were deported to a godforsaken territory and left there without any help. So one could say that the Hayırsızada Dog Massacre somehow foretold the Armenian Genocide. The author of this article refers to different works of art (such as Psy z Üsküdar/ The Dogs of Üsküdar – a joint work created by Joanna Rajkowska and Sebastian Cichocki, or Chienne d‘histoire – a short animation directed by Serge Avédikian, and several others), which try to remind us about the massacre of the homeless dogs in Istanbul. It is also worth mentioning that, in the descriptions of the massacres of Armenians which preceded the Armenian Genocide, associations with the killing of animals are very common.